2021
DOI: 10.3389/fimmu.2021.718603
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Models of Infectious Pulmonary Complications Following Hematopoietic Cell Transplantation

Abstract: Pulmonary infections remain a major cause of morbidity and mortality in hematopoietic cell transplantation (HCT) recipients. The prevalence and type of infection changes over time and is influenced by the course of immune reconstitution post-transplant. The interaction between pathogens and host immune responses is complex in HCT settings, since the conditioning regimens create periods of neutropenia and immunosuppressive drugs are often needed to prevent graft rejection and limit graft-versus-host disease (GV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 126 publications
(154 reference statements)
2
3
0
Order By: Relevance
“…In contrast, the chemotherapy group was dominated by common Gram-positive cocci. Similar findings have also shown that pseudomonas aeruginosa is more prevalent after allo-HSCT and in immunocompromised patients, but is not an independent risk factor for it ( Di Pasquale et al., 2019 ; Zhou and Moore, 2021 ). Among the fungal infections, Aspergillus infections were more common in both groups, and Mucor and Candida were less common.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In contrast, the chemotherapy group was dominated by common Gram-positive cocci. Similar findings have also shown that pseudomonas aeruginosa is more prevalent after allo-HSCT and in immunocompromised patients, but is not an independent risk factor for it ( Di Pasquale et al., 2019 ; Zhou and Moore, 2021 ). Among the fungal infections, Aspergillus infections were more common in both groups, and Mucor and Candida were less common.…”
Section: Discussionsupporting
confidence: 76%
“…In terms of empirical anti-infection treatment of patients, HHV5 (CMV) was the most common virus infection in the transplantation group, while HHV7 was the most common in the chemotherapy group. Among the bacterial infections, Pseudomonas aeruginosa and Streptococcus pneumoniae were most common in the transplantation and chemotherapy groups, respectively, which may be related to the pretreatment regimen medication and long application of immunosuppressive agents in patients in the transplantation group, and it is prone to the infection of Gram-negative bacilli ( Zhou and Moore, 2021 ). In contrast, the chemotherapy group was dominated by common Gram-positive cocci.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In murine models of allogeneic HCT, immune responses to pathogens can be both impaired as well as exaggerated, leading to delayed phagocytosis, excessive myeloid cell recruitment and unremitting inflammation due to a lack of functional NK-and T-cells. [79][80][81][82] Our data support this paradigm in human patients and reveal a complex and heterogeneous immune response. Cluster 1, with a replete and diverse pulmonary microbiome, showed the lowest mortality rates, low levels of granulocyte activation, and low levels of lymphocyte diversity and lymphocyte-specific activation markers.…”
Section: Discussionsupporting
confidence: 74%
“…The relationship between the pulmonary microbiome, lung epithelium and the transplanted immune system is characterized by a continuous mutually influential interaction. In murine models of allogeneic HCT, immune responses to pathogens can be both impaired and exaggerated, leading to delayed phagocytosis, excessive Article https://doi.org/10.1038/s41591-024-02999-4 myeloid cell recruitment and unremitting inflammation because of a lack of functional natural killer and T cells [56][57][58][59] . Our data support this paradigm and reveal a complex heterogeneous immune response.…”
Section: Discussionmentioning
confidence: 99%